The Space Groups and Collaborative Assembly (EAAE Joint Publishings, 2026)
This investigation reviews an unexpected outcome arising from using a tool for algorithmic design for a human fabrication project. The Space Groups are a mathematical system for describing repetitive 3d Unit Geometries commonly used in crystallography. Horta is a Grasshopper library which adapts these methods to define elements within a Unit Cell and output terse instruction sets for distributing these across a lattice to create complex honeycombs. Originally intended for automated assembly in the Computationally Optimized Robotic Architecture Laboratory (CORAL), it was found that Horta also facilitates collaborative human assembly. Workshops were delivered at CAAD Futures 2021 to help educate architects about the use of Symmetries in design - specifically the use of the Space Groups as design tool via the units generated by Horta. The COVID-19 pandemic resulted in the Conference and Software Workshop shifting online. The original design for the Fabrication Workshop was predetermined. Without in-person Conference participants or facilities available, an ad-hoc group of volunteers gathered and through shared effort, an unanticipated potential for discrete modular assembly emerged. When the Workshop goals were simplified, the design became open-ended - the final design emerging bottom-up from the collaborative assembly process. Horta was developed to generate “algorithmic” instructions for automated assembly. However during the Fabrication Workshop it was found that applying this system allowed a “heuristic” collaborative design method to emerge. This opened participation to the untrained, even a child. The algorithmic methods of the system directly facilitated the adaptive heuristic methods of a community fabrication project. This paper briefly explains the Space Group Symmetries and then outlines the Workshops. It finishes by examining the outcomes of the Fabrication Workshop. Both the last-minute adaptation to the pandemic restrictions and the surprise outcome of a heuristically-driven community design effort are apt for examination along the 2024 EAAE- ARCC Conference theme Architecture Into The Unknown.